Exploration of testing practices and population characteristics support an increase in chlamydia positivity in Tasmania between 2001 and 2010. (29th December 2015) - Stephens, Nicola; Coleman, David; Shaw, Kelly; O'Sullivan, Maree; Vally, Hassan; Venn, Alison
Abstract: Objective : The proportion of positive chlamydia tests in young people in Tasmania increased significantly between 2001 and 2010. While female positivity rates increased steadily, male positivity rose steeply to 2005 then stabilised. Crude positivity rates can be influenced by a variety of factors making interpretation difficult. Unique Tasmanian datasets were used to explore whether symptom status, reason for testing or sexual exposure could explain the observed positivity trends. Methods : Population‐level chlamydia positivity rates in Tasmania over a 10‐year period were compared with surveillance data collected on people aged 15 to 29 years notified with chlamydia. Results : The proportion of asymptomatic chlamydia cases increased, with the largest increase in males aged 15 to 19 years (28%). Opportunistic testing of cases increased (greatest in males, range 17–32%). Sexual exposure remained consistent. Conclusions : After allowing for any changes in sexual exposure, symptom status and reason for testing, an increase in chlamydia positivity occurred over the 10 years. Healthcare providers have increased chlamydia testing in high‐risk groups. Implications : Monitoring chlamydia testing patterns and positivity rates at a population level is a step forward in surveillance practices. Targeted surveys provide valuable information to supplement routine surveillance data.